Maximal Clifford Semigroups of Matrices - Lee, Edmond W. H. (Sarajevo Journal of Mathematics, 2024)
All maximal Clifford semigroups of matrices are identified up to isomorphism. If the ground field of the matrices is finite, then there exists a unique Clifford semigroup of maximum order. 2000 Mathematics Subject Classification. 20M25